Blame it on Barbie: body figure preferences and disordered eating amongst adolescent South African females, a cross cultural study - Davies, Sally (My University, 1995)
In recent years there has been great interest in studying the energy-restrictive eating disorders within sociocultural contexts. Patterns of change in the incidence and prevalence of these disorders appear to reflect social processes involving gender issues and shared cultural values around the female body, South African society is experiencing rapid sociocultural changes, and this raises questions about disordered eating and values our own society. This study investigated body figure preferences and attitudes and behaviours related to eating and body weight. The sample consisted of 125 White pupils and 61 Black pupils in three high schools in urban and periurban areas of Gauteng, South Africa. The schools represent different socioeconomic Environments. One is a private school and one is state school with partial provincial subsidy in an affluent suburb, and one is a community school which is subsidised mainly by donor funding and serves a periurban Community. Black and White pupils reported similar body ideals and levels of discrepancy between their reported actual body figures and their ideal figures, but Black pupils showed significantly greater tolerance of different body figures. both thin and fat. Despite this increased tolerance. However, their scores on the Eating Disorders Inventory were similar to those of the White pupils and exceeded White pupils on perfectionism and maturity fears measures, Amongst Black pupils in the three schools. EDI scores were similar but State school pupils showed more body dissatisfaction and Community school pupils showed more perfectionism; and maturity fear, This suggests that pupils in more disadvantaged school environments are weight-concerned and could still be at risk of disordered eating, the finding is contrary to expectations that private school pupils would show the most disordered eating and weight concern. EDI scores were closely related to body figure preferences, and especially to real-ideal discrepancy which was shown to be a simple but effective measure, A high-scoring subgroup was isolated and this was found to include 14 Black pupils and 22 White pupils, The findings have implications for preventive efforts and for further research,
A research report submitted to the Faculty of Arts, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the Degree of Masters of Arts, (Clinical Psychology) Johannesburg, 1995.
Keywords: Body image in adolescence--South Africa; Eating disorders in adolescence--South Africa